The Transition Period in Bulgaria in the Collective Memory of the Postcommunist Generations - Simeonova, Elena (Research Papers, 2019)
The article presents the results of a typological study of the collective memory about the transition in Bulgaria after 1989, which has been held since 2008 among students from UNWE. The main objective is to analyze the change in the recent past memories in the minds of the young generations. It seeks to answer the question of what provokes the collective amnesia for key events and personalities from the transition period.
Keywords: Collective memory; Post communism; Transition